2023
DOI: 10.3389/fneur.2022.1098857
|View full text |Cite
|
Sign up to set email alerts
|

The potential roles of dental pulp stem cells in peripheral nerve regeneration

Abstract: Peripheral nerve diseases are significantly correlated with severe fractures or trauma and surgeries, leading to poor life quality and impairment of physical and mental health. Human dental pulp stem cells (DPSCs) are neural crest stem cells with a strong multi-directional differentiation potential and proliferation capacity that provide a novel cell source for nerve regeneration. DPSCs are easily extracted from dental pulp tissue of human permanent or deciduous teeth. DPSCs can express neurotrophic and immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Previous studies have demonstrated DPSCs show the potential therapies for SCI through multiple mechanisms, mainly involving neuronal differentiation, paracrine effects and exosome secretion ( Xu et al, 2019 ; Bonaventura et al, 2020 ; Fu et al, 2023 ) ( Figure 2 ).…”
Section: The Potential Mechanisms Of Dpscs In Scimentioning
confidence: 96%
See 2 more Smart Citations
“…Previous studies have demonstrated DPSCs show the potential therapies for SCI through multiple mechanisms, mainly involving neuronal differentiation, paracrine effects and exosome secretion ( Xu et al, 2019 ; Bonaventura et al, 2020 ; Fu et al, 2023 ) ( Figure 2 ).…”
Section: The Potential Mechanisms Of Dpscs In Scimentioning
confidence: 96%
“…Isolated DPSCs can not only maintain and repair periodontal tissue, with the feature of high proliferation rate, but also show plasticity in multi-lineage differentiation. Several in vitro studies have confirmed DPSCs have the potential to differentiate into multiple cell types such as osteoblasts-, chondrocytes-, adipocytes-, odontoblasts-, neural- and myocytes-like cells ( Fu et al, 2023 ) ( Figure 2 ).…”
Section: Biological Characteristics Of Dpscsmentioning
confidence: 99%
See 1 more Smart Citation
“…DPSCs, first derived from the dental pulp in 2000 by Gronthos [ 51 ], share characteristics with mesenchymal stem cells, including plasticity, adhesiveness, and a fibroblast-like morphology [ 45 ]. Notably, DPSCs express neurotrophic and immunomodulatory factors, promoting blood vessel formation and nerve regeneration [ 52 ].…”
Section: The Neurodegenerative Potential Of Dental Stem Cellsmentioning
confidence: 99%
“…These neurotrophic components may help injured axons survive longer and encourage their regeneration. It has been demonstrated that transplanting SCs seeds into a nerve conduit can improve axonal regeneration ( 71 , 72 ). The utilization of autologous stem cells in clinical settings is limited due to various factors, such as the occurrence of morbidity at the donor site, challenges associated with acquiring and rapidly expanding a substantial quantity of stem cells, the requirement for sequential surgical procedures with short intervals (one for harvesting and expanding stem cells and another for nerve gap repair), and the decline in stem cell numbers with advancing age ( 73 ).…”
Section: Graft Materialsmentioning
confidence: 99%